CRITICAL STUDY OF ELECTION FRAUD IN THE PERSPECTIVE OF ELECTION LAW - Candra Lolita, Margareta; Kayana Putri, Nairah; Ainurrohma, Mardiana; Renatha Dias, Jovanda (KELOMPOK KOMUNITAS LABORATORIUM PENELITIAN-COMMUNITY OF RESEARCH LABORATORY, 2024)
Election fraud is one of the crucial issues that can damage the integrity of democracy in Indonesia. This study aims to critically examine various forms of election fraud from the perspective of the Election Law, especially how existing regulations regulate prevention, supervision, and handling. Using a juridical-normative approach, this study analyzes related legal provisions, including Articles in Law No. 7 of 2017 concerning Elections, and their relevance to implementation in the field. The results of the study indicate that although regulations have been designed to create honest and fair elections, weaknesses in aspects of law enforcement, supervision, and transparency are still loopholes for violations. In addition, the involvement of political figures and the weak legal awareness of the community have exacerbated this problem. This study recommends strengthening regulations, optimizing technology-based supervision, and political steps to the community as strategic steps to prevent election fraud in the future.